NONLINEARITY OF HIGHER EDUCATION DEVELOPMENT: THE CONTOURS OF THE CONCEPT AND POSSIBLE MACROREGIONAL PRACTICES - Garold E. Zborovskiy; Еlena A. Shuklina; Polina A. Ambarova (Moscow Polytechnic University, 2016)
Abstract. The article discusses the need to replace the conception of linear development of higher education with a conception of its nonlinear development. It is conditioned by social and economic uncertainty and nonlinearity of social development. The authors identify the main characteristics of the nonlinear way of higher education development. The central thesis of this paper is that the educational communities should be viewed as the core, systemforming factor of higher education. The paper emphasizes that the prospects for this type of education are associated with a nonlinearity of it development. On the materials of the particular macroregion - Urals Federal District - it is proved that the nonlinearity of higher education may have a macroregional character.